(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Rishi Valmiki was the first to forge the grand form of Itihasa and to create a unique prosodic pattern for the epic literary genre of the Ramayana. As time goes on, people experience stress, frustration, mental and physical illnesses, a lack of brotherhood, a lack of religious practice, a lack of love for the natural world and its creatures, and a lack of moral and ethical principles. Objectives: The study aims to determine how applicable the Ramayana is to modern society and how it affects our daily lives. Methods: This study has taken a qualitative approach and is descriptive, drawing on secondary data for its design. Results and Discussion: Several key takeaways from the Ramayana are examined, including how Dharma affects our lives. People acquire skills such as accountability, social duty, authenticity, and other related ones. Findings: The computerised lives of people in the modern era can be drastically changed by the timeless relevance of ancient epics such as the Mahabharata and the Ramayana. Conclusion: In actuality, the Ramayana offers insightful lessons that we can apply to to our day-to-day existence without any complicity. All situations—individual, familial, and broader aspects of social and professional ambiguities—can benefit from these solutions.